Towards obtaining the optimum physical, optical and nuclear radiation attenuation behaviours of tellurite–germanate glasses through Eu2O3 reinforcement: Glass synthesis, experimental and theoretical characterisation study - Mattos, G. R.S.; Bordon, C. D.S.; Kassab, L. R.P. [UNESP]; Issa, Shams A.M.; ALMisned, Ghada; Tekin, H. O. (Elsevier, 2023)
We report the physical, optical and nuclear radiation attenuation behaviours of tellurite–germanate (TeO2–GeO2–PbO) glasses reinforced with varying amounts of Eu2O3. The samples were synthesised using the conventional melt-quenching method and had the following composition (in wt.%): 33.34TeO2 - 33.33GeO2 - 33.33PbO (TGP). Different concentrations of Eu2O3 (in wt.%) were added to the glass composition, labelled TGP1, TGP2 and TGP3. The physical, optical and nuclear radiation attenuation properties were measured using both experimental and theoretical methods. At room temperature, the visible to near-infrared optical absorption spectrum ranged from 400 to 900 nm. The TGP1 sample with 1 wt% The Eu2O3 additive exhibited the lowest absorbance and the highest transparency. The TGP1 sample also exhibited the highest nuclear radiation absorption properties. The gamma-ray absorption capabilities of TGP1 were demonstrably superior to those of various types of glass shields and other old- and new-generation concrete-shielding materials. Thus, adding 1 wt% Eu2O3 to tellurite–germanate glasses would ‘improve nuclear radiation absorption and optical properties. It can also be concluded that expanded scientific community investigations in this area would be a significant step toward gaining a deeper understanding of these glass structures and determining what other optimisation tasks the addition of 1 wt% Eu2O3 can accomplish.
Keywords: Glass shields; Optical properties; Radiation protection; Tellurite–germanate glasses